Implementasi Bimbingan Spiritual pada Anak Usia Dini Melalui Kisah Uwais Al-Qarni di TPA Safinatussafa, Aceh Selatan, Indonesia - Miftahul Jannah; Maemonah Maemonah (DAYAH: Journal of Islamic Education, 2022)
This article discusses the cultivation of spiritual values in early childhood through the story of Uwais Al-Qarni at TPA Safinatussafa, LhokAman. Early childhood is a crucial period in shaping a child's personality. Early childhood is a golden age where children have all the potential that must be developed. Cultivation of spiritual values is carried out through group spiritual guidance. This study employed qualitative research using a phenomenological approach. In the story of Uwais Al-Qarni, several spiritual values can be instilled in early childhood, including filial piety, humble, not worldly oriented (zuhud), patience, and love for the Prophet. The research results showed that there were changes in children that impacted their personalities for the better. The children who show this can interact well with their friends, are more polite, respect their parents and ustazahs, and do not speak harshly.